Science Literacy of Senior High School Students through Pacu Jalur Tradition Based Learning - Deni Elsya Widya; Z. Zulirfan; Y. Yennita (Journal of Indonesian Science Teachers, 2024)
This research intends to look at the level of scientific literacy of high school students through learning based on the Pacu Jalur Tradition. Quasi-experiment was used as a method in this research with a nonequivalent posttest-only control group design. The population in this search was class XI students of SMAN 1 Teluk Kuantan, totaling 143 people. There were 71 students as samples for this research divided into experimental class and control class. Learning with an approach based on the Pacu Jalur Tradition is implemented in the experimental class, while conventional learning is applied in the control class. The research instrument was a scientific literacy test consisting of 20 multiple-choice questions arranged based on scientific literacy competencies according to PISA 2018. The scientific literacy post-test was carried out after learning about the dynamics of rectilinear motion had been completed in both classes. Data from the scientific literacy post-test results were analyzed descriptively and inferentially. The results of data processing show that there is a difference in the mean score of the experimental class, namely 74.29 (good category), and the mean score of the control class of 57.08 (enough category). The Independent Sample t-test carried out obtained sig. 0.00<0.05. The results of this research prove that the use of a learning approach based on the Pacu Jalur Tradition is effective in increasing the scientific literacy of senior high school students.